2020
DOI: 10.24018/ejbmr.2020.5.5.583
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Government Expenditures and Revenues in Algeria During the Period (1990-2019): Granger Causality Approach

Abstract: The aim of this study is to examines the causal relationship between government revenues and expenditures in Algeria during the period 1990 to 2019. Data properties were analyzed to determine their stationarity using the Dickey-Fuller (ADF) test, Phillips-Perron test and Kwiatkowski, Phillips, Schmidt, Shin (KPSS) test, as well as the Granger Causality Test (1969) of showing the direction. The results show that there is unidirectional causal relationship between government expenditure and revenue with the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Firstly, the earn-and-spend hypothesis (or tax-spend, or revenue dominance hypothesis) proposed by Buchanan and Wagner (1977) and Friedman (1978) argue the existence of a unidirectional causality flow from government revenue to government expenditure. Similar studies have also confirmed this hypothesis , Yinusa and Adedokun (2017) in Nigeria; Rezaei (2015) in Iran; Sahed et al (2020) in Algeria). Secondly, the spend-and-earn hypothesis (or spend-tax or expenditure dominance hypothesis) led by Wiseman (1961, 1979) states that there is a unidirectional causality from government expenditures to revenue.…”
Section: Introductionsupporting
confidence: 71%
“…Firstly, the earn-and-spend hypothesis (or tax-spend, or revenue dominance hypothesis) proposed by Buchanan and Wagner (1977) and Friedman (1978) argue the existence of a unidirectional causality flow from government revenue to government expenditure. Similar studies have also confirmed this hypothesis , Yinusa and Adedokun (2017) in Nigeria; Rezaei (2015) in Iran; Sahed et al (2020) in Algeria). Secondly, the spend-and-earn hypothesis (or spend-tax or expenditure dominance hypothesis) led by Wiseman (1961, 1979) states that there is a unidirectional causality from government expenditures to revenue.…”
Section: Introductionsupporting
confidence: 71%
“…Al-Zeaud (2015), Elyasi dan Rahimi (2012), Mehrara, Pahlavani, and Elyasi (2011) menunjukkan bahwa terdapat hubungan kausalitas dua arah antara penerimaan dan pengeluaran pemerintah. Akan tetapi bertetangan degan hasil penelitian Sahed, Mékidiche, and Kahoui (2020), Mehrara and Rezaei (2014), dan Eita and Mbazima (2008) yang menyatakan bahwa hanya terdapat hubungan kausal searah antara penerimaan dan pengeluaran pemerintah yang bejalan dari penerimaan menuju pengeluaran pemerintah. Sedangkan menurut penelitian Ali and Syah (2012), dan Anne Sere and Choga (2017) menunjukkan bahwa tidak terdapat hubungan kausalitas jangka panjang ataupun pendek antara penerimaan pemerintah dan pengeluaran pemerintah.…”
Section: Sumber: Badan Pusat Statistik 2019unclassified
“…Although the national specificity of the state's responsibility and involvement is a significant factor in defining fiscal policy, the causality between revenue and expenditure has highlighted mixed results. On the one hand, empirical research shows that, in the long term, in less developed countries, government expenditure cause the revenue (Lojanica, 2015), but also that government revenue can cause the expenditure (Sahed, Mékidiche, & Kahoui, 2020).…”
Section: Introductionmentioning
confidence: 99%